Resepsi Masyarakat Terhadap Al-Quran: Pengantar Menuju Metode Living Quran - Muhammad Amin; Muhammad Arfah Nurhayat (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2020)
Al-Quran has been a part of human life since it was first revealed and has been accepted by society. In Indonesia, the reception can be in the form of aesthetic receptions, cultural receptions, and academic receptions. Some forms of cultural receptions that are developed in the community still contain elements of local culture. As a means of forming cultural understanding, especially local culture that uses the Koran as a part of it, a special cultural methodology is needed. This method is known as the Living Quran method. This method is a study of culture with two steps, namely the historical-normative analysis and the socio-cultural analysis of the people who own the culture.